‘I am discriminated against because I exist’: Psycho-emotional effects of multiple oppressions for disabled women in Iceland - Freyja Haraldsdóttir 1986- (2017)
Disabled women across the globe have experienced multiple oppressions on the grounds of gender, disability, age, class, race, sexuality and other factors through the decades. It has prevented them from equal opportunities and deprived them of physical and psychological wellbeing. In this master’s thesis I have explored disabled women's experience of multiple oppressions in Iceland with emphasis on gender and disability. Also the psycho-emotional effects of being subjected to different manifestations of direct and indirect violence and in what way the women resist as well as looking at their recommendations for social change. The findings suggest that the disabled women experience multiple forms of oppression in various spaces and often in subtle and injuring ways. The psycho-emotional effects are complicated and paradoxical, but present themselves through exhaustion, sadness, anxiety and fear, as well as anger, feelings of powerlessness, dependency, sexual objectification and dehumanisation. The women resist and heal in different ways, e.g. reclaiming self-identification, reaching out to friends and family who validate their experience and through solidarity with other disabled women. They believe the way forward is to influence marginalizing power structures and harming ableist and sexist cultures in society that prevents disabled women in Iceland from full inclusion and human rights. Fatlaðar konur um allan heim hafa orðið fyrir margþættri mismunun á grundvelli kyngervis, fötlunar, aldurs, stéttar, kynþáttar, kynheigðar og kynvitundar frá upphafi. Það hefur komið í veg fyrir jöfn tækifæri þeirra og dregið úr líkamlegri og andlegri vellíðan. Í þessari meistararitgerð hef ég rannsakað reynslu fatlaðra kvenna á Íslandi af margþættri mismunun með sérstakri áherslu á kyngervi og fötlun. Jafnframt hef ég skoðað sálrænar afleiðingar af því að verða fyrir margskonar beinu og óbeinu ofbeldi, hvernig konurnar andæfa slíku ofbeldi og hverjar hugmyndir þeirra eru af samfélagsumbótum. Niðurstöður rannsóknarinnar gefa til ...